Procedimentos e testes de manutenção elétrica em subestações abrigadas de 13,8 kV - Belleza, Kevin Cardenas (Brasil, 2021)
Traditional industrial maintenance techniques have undergone great advances in recent years due to the need to minimize the unavailability of manufacturing machines, caused by the lack of preservation of their assets. With technological growth, advanced equipment analysis techniques were developed, allowing industrial maintenance sectors to adopt them in their processes. This development of new techniques has left the application of corrective maintenance in disuse, allowing the emergence of preventive and predictive maintenance, the latter being non-invasive. Preventive maintenance is the main theme of this work, and its application in sheltered 13.8kV substations is addressed. Therefore, this work aims to explain modern techniques for preventive maintenance of substation equipment, through a methodology and testing procedures, as well as through a simple case study, in such a way that allows the reader to understand the subject in a simple way. main approach in this work.